Pengaruh Pijat Oksitosin pada Ibu Nifas untuk Meningkatkan Produksi ASI - Vina Sutratul Putri; Riona Sanjaya; Komalasari Komalasari; Inggit Primadevi (Universitas Muhammadiyah Manado, 2025)
The smooth production of breast milk is a major factor in the success of exclusive breastfeeding. According to an Indonesian survey, 38% of moms quit nursing because their breast milk production was insufficient. The fifth to sixth costae bones are massaged along the vertebrae of the spine during an oxytocin massage. The purpose of oxytocin massage is to keep the mother comfortable, promote the release of the hormone oxytocin, and sustain the production of breast milk. This research objective was to determine the effect of oxytocin massage on breast milk production in postpartum mothers at the Jadimulyo Village Health Post. The research type is quantitative with a quasi-experimental design with a nonequivalent control group design. The population of this study were postpartum mothers at the Jadimulyo Village Health Post whose breast milk production was low in August. The sample consisted of 20 people with details of 10 people in the experimental group and 10 people in the control group. The sampling technique was consecutive sampling. This study was conducted at the Jadimulyo Village Health Post of Sekampung Sub-District East Lampung. The experimental group was given oxytocin massage for five days in the morning and evening. While the control group was given breast care. Data collection used observation sheets, and analysis used the Man Whitney test. The study results showed that there was an effect of oxytocin massage on postpartum mothers to increase breast milk production at the Jadimulyo Village Health Post of Sekampung Sub-District, East Lampung in 2024 with a p-value = 0.000. Suggestions for health workers to socialize the oxytocin massage technique. So, mothers and families can apply it at home.